Peran Perempuan dalam Meningkatkan Pengawasan Partisipatif Masyarakat pada Pilkada Tahun 2024 di Kota Metro - Umniyatus Selfiyana; Muhtadi Muhtadi (CV Rewang Rencang, 2025)
This study explores the role of women in strengthening participatory monitoring in the 2024 Regional Head Election (Pilkada) in Metro City. Using a juridical-empirical approach, the research reveals that women play a strategic role in safeguarding electoral integrity, promoting inclusive political participation, and ensuring a transparent democratic process. Findings indicate that women's involvement remains limited, from village-level election monitors to Bawaslu commissioners. Therefore, affirmative support, political education, and equal participatory space are essential to enhance women's roles in sustainable election monitoring.